HLA-DR antigens on human macrophages from bronchoalveolar lavage fluid. Issue 4 (April 1986) - Costabel, U; Bross, K J; Andreesen, R; Matthys, H
Abstract : The expression of HLA-DR (Ia-like) antigens on human macrophages was investigated by analyses of cells from bronchoalveolar lavage fluid obtained from 12 patients with pulmonary sarcoidosis, six patients with extrinsic allergic alveolitis, nine patients with cryptogenic fibrosing alveolitis, 11 normal non-smokers, and 12 normal smokers. The HLA-DR antigen was demonstrated by the mouse monoclonal antibody OKIa by a peroxidase-antiperoxidase method performed on glass slides. No differences were found in the percentage of alveolar macrophages that expressed DR antigens between the five study groups. OKIa positivity was observed on more than 90% of macrophages in all cases. These observations suggest that the previously reported enhanced antigen presentation by alveolar macrophages in sarcoidosis is not linked with an increase in the percentage of DR+ macrophages in the lung.